2005
DOI: 10.1107/s1600536805015357
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Diphenyl-2-(quinolin-8-yloxy)acetamide monohydrate

Abstract: In the title compound, C23H18N2O2·H2O, all bond lengths and angles are within normal ranges. The dihedral angles formed by the two phen­yl rings with the quinoline moiety are 61.40 (9) and 85.66 (8)°. The crystal packing is stabilized by inter­molecular C—H⋯O and O—H⋯O hydrogen bonds involving the solvent water mol­ecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Recently, we have reported the structure of an amide-type acyclic compound with an 8-hydroxyquinolinate skeleton, namely N,N-diphenyl-2-(quinolin-8-yloxy)acetamide monohydrate, (II) (Wen et al, 2005). In order to investigate the effect of the substituent groups of the acyclic compounds on the coordination selectivity and extractability for metal ions, we have synthesized and carried out the structure determination of the title compound, (I).…”
Section: Commentmentioning
confidence: 99%
“…Recently, we have reported the structure of an amide-type acyclic compound with an 8-hydroxyquinolinate skeleton, namely N,N-diphenyl-2-(quinolin-8-yloxy)acetamide monohydrate, (II) (Wen et al, 2005). In order to investigate the effect of the substituent groups of the acyclic compounds on the coordination selectivity and extractability for metal ions, we have synthesized and carried out the structure determination of the title compound, (I).…”
Section: Commentmentioning
confidence: 99%
“…For related literature, see: Allen et al (1987); Bratzel et al (1972); Li et al (2005); Patel & Patel (1999); Wen et al (2005).…”
Section: Related Literaturementioning
confidence: 99%
“…Recently, the structures of the unsubstituted 8-hydroxyquinolinate amide-type compounds, namely Nphenyl-2-(quinolin-8-yloxy)acetamide, (II) (Li et al, 2005) and N,N-diphenyl-2-(quinolin-8-yloxy)acetamide, (III) (Wen et al, 2005) have been reported. Here, we have synthesized and carried out the structure determination of the title compound, (I) ( Fig.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For related literature on unsubstituted 8-hydroxyquinolinate amide compounds, see: Li et al (2005); Wen et al (2005). For applications of 8-hydroxyquinoline derivatives, see: Bratzel et al (1972); Patel & Patel (1999).…”
Section: Related Literaturementioning
confidence: 99%